Sowing seeds of partnership: Ethiopia and IITA explore new frontiers in agricultural innovation - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2025)
The Ethiopian Ambassador to Nigeria, His Excellency Ambassador Legesse Geremew Haile, accompanied by his spouse and the Minister Counsellor, Misgna Teklu Abrha. Their visit was to deepen their understanding of IITA’s research activities and explore opportunities for collaboration between Ethiopia and IITA Ambassador Legesse appreciated the warm reception, noting that IITA felt like home. He commended the visible impact of the institute’s research across the continent and reaffirmed Ethiopia’s commitment to improving livelihoods through agriculture. “Changing lives and lifting people out of poverty is not easy, especially when agriculture is underperforming. The Ethiopian government is committed to professionalizing the agricultural sector because we cannot overcome poverty without achieving food security,” he remarked. He emphasized his interest in learning from IITA’s successes and fostering meaningful partnerships during his tenure in Nigeria.